Law and childhood studies - Freeman, Michael D. A. (Oxford : Oxford University Press, 2012)
Offering an insight into the evolving state of law and childhood studies in the modern age, this volume in the 'Current Legal Issues' series brings together an international and interdisciplinary cast to address the key issues informing current debates.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Children -- Legal status, laws, etc; Minors; Age (Law)